Report From the International Society of Urological Pathology (ISUP) Consultation Conference on Molecular Pathology of Urogenital Cancers V: Recommendations on the Use of Immunohistochemical and Molecular Biomarkers in Penile Cancer. (July 2020) - Canete-Portillo, Sofía; Velazquez, Elsa F.; Kristiansen, Glen; Egevad, Lars; Grignon, David; Chaux, Alcides; Cubilla, Antonio L.
Abstract : Penile cancer and its precursor lesions are morphologically and clinically heterogenous and they can be further characterized by immunohistochemical (IHC) and molecular genetic analyses. According to the current World Health Organization (WHO) classification, penile intraepithelial neoplasia (PeIN) and invasive penile carcinomas can be grouped into human papillomavirus (HPV)-related and non–HPV-related neoplasms. This distinction is clinically relevant for etiological and prognostic reasons. To gain insight into the current use of molecular testing and IHC in their diagnostics, a survey was held among the membership of the International Society of Urological Pathology (ISUP). About 250 pathologists from 51 countries answered the survey on the practice and use of IHC/molecular technique as aids in the diagnosis of penile squamous neoplasia. More than half (60%) of the respondents worked at an academic hospital. The questions focused on condylomas, precancerous squamous lesions, and squamous cell carcinoma (SCC). About 35% to 45% of the pathologists considered the use of IHC or molecular tests of value in the pathologic evaluation of precancerous and invasive neoplasms. The vast majority of the respondents do not use IHC for the diagnosis and subtyping of condylomas. There is emerging evidence that some condylomas may participate in the penile carcinogenesis process, especially the high-risk HPV-related atypical condylomas. We recommend the use of p16 in such cases. For most PeIN cases, about half of the responding pathologists make the diagnosis on hematoxylin and eosin slides only. For their subtyping, 50% to 55% of the pathologists use IHC in warty or basaloid PeINs and 40% in differentiated PeIN. To separate HPV-related PeIN from non–HPV-related PeIN, 80% reported using p16 and 20% Ki-67. On the basis of literature review and our practice, the ISUP working group recommends the use of Ki-67 to separate non–HPV-differentiated PeIN from squamous hyperplasia and the use of p16 to distinguish the pleomorphic variant of differentiated PeIN from HPV-related PeIN. With respect to SCCs, according to the survey, immunostaining is only applied in 15% of conventional invasive SCCs, the majority being diagnosed by hematoxylin and eosin. To separate HPV and non-HPV tumors, most (80%) would use p16 and 25% would use p53. For subtype classification, they consider IHC necessary to identify verrucous, papillary, warty, warty-basaloid, and basaloid carcinomas. p16 is used as a surrogate of polymerase chain reaction for the identification of high-risk HPV. We recommend the use of p16 immunostain in cases where the tumoral histologic features of the SCCs are not classical for HPV-related neoplasms, especially in poorly differentiated tumors. Because the majority of these neoplasms harbor high-risk HPV (HPV16), identifying the presence of the virus is rather more important than documenting its specific genotype.